ANALYSIS OF THE TEACHERS AND ADOLESCENTS OPINIONS REGARDING 14-15 YEARS OLD STUDENTS ATTITUDE TOWARD PHYSICAL EDUCATION LESSONS - Irina Delipovici; Ion Moroșan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
As a result of investigating teachers and adolescents it was obtained new results on student attitude toward physical education lessons. Most teachers claim that 14-15 years old students show an average interest for the discipline "Physical Education", assessing their readiness analog and driving. However, the vast majority of teachers involved in the teaching of this subject indicate that there are some difficulties in teacher training process with adolescents. Only ½ of the adolescents are satisfied with the organization and conduct of those lessons, and many of them have no confidence in their skills, although physical education lessons can be effective in this regard.